Management of Tracheal Perforation following Anterior Cervical Spine Surgery: Report of Two Cases and Review of the Literature - Xinhu Guo; Hongquan Ji (Case Reports in Orthopedics)
Background. Tracheal perforation is a complication very rare but challenging that follows anterior cervical spine surgery. This article describes the management of tracheal perforation due to instrument failure after anterior cervical spine surgery performed in two patients because of fracture dislocation of the subaxial cervical spine. Case Presentation. Two patients who suffered from a subaxial cervical fracture and dislocation were subjected to anterior cervical spine surgery for fracture reduction and cervical fusion. However, instrumentation failure occurred in both patients, resulting in implant displacement and penetration into the posterior tracheal wall. Revision surgery consisted of fracture reduction, multilevel posterior fixation, and removal of the displaced anterior cervical implants. Tracheal perforation was bypassed by placing a tracheostomy tube in a caudal position for the diversion of the airflow and tracheal hygiene. The thorough debridement and drainage performed in both patients allowed a complete healing of the anterior wound in both of them, with no sign of infection or subcutaneous emphysema, as confirmed by postoperative CT scan and flexible bronchoscopy. Both patients acquired a solid fusion of the cervical spine at last follow-up (16 months and 24 months). Conclusions. The perforation of the trachea after anterior cervical spine surgery due to the displacement of the implants could be managed using posterior cervical instrumentation and fusion, the removal of the anterior implant, debridement and drainage, and the use of a distal bypassing tracheostomy tube.